Developing of basic scientific process skills by using Inquiry based Learning (5E) with games for grade 5 students - Ploensombat, Saranya; Saeng-ngam, Kanyawadee (Journal for Developing the Social and Community, 2023)
The purpose of this research was to develop basic scientific process skills by using inquiry based learning (5E) with games with games. 70% of the students in grade 5 passed the criteria by applying the process of conducting an action research according to Kurt Lewin's concept. The target group was 8 grade 5 students. The research instruments were: 1. Lesson Plans using inquiry based learning (5E) with games. 2. A basic science process skills assessment form; and 3. An observation form for student learning behavior. Data were analyzed from the Basic Science Process Skills Assessment Form. by averaging and standard deviation by percentage against criteria The data obtained from the observation form of student learning behavior were analyzed, processed, compiled and presented in an essay format. The results showed that all 8 students (100%) had score higher than the required scores on basic scientific process skills. Passed the criteria of 70% or more.